The role of sovereign credit ratings in fiscal discipline - Duygun, Meryem; Ozturk, Huseyin; Shaban, Mohamed (Elsevier, 2016)
This paper investigates several aspects of the relationship between sovereign credit ratings and fiscal discipline. The analysis of over one thousand country–year observations for 93 countries during the 1999–2010 period reveals that a country’s debt level is likely to increase with higher ratings, confirming the existence of pro–cyclicality and path dependence of ratings. In addition, the study finds no evidence to support the theory of Political Business Cycle, which implies that political ambitions may lead to fiscal worsening following a rating upgrade. The study findings further demonstrate that institutional quality is an important factor in the ratings–fiscal discipline nexus.